Response of growth and production of pakcoy (Brassica rapa L.) through hydroponic system with different types of planting media and aeration - Rona Charitsabita; Endang Dwi Purbajanti; Didik Wisnu Widjajanto (Jurnal Pertanian Tropik, 2019)
The use of appropriate planting media and suitable aeration in hydroponic crop cultivation need to be considered to produce maximum plant growth and production. The research was aimed to examine the interaction between planting media and aeration on the growth and production of pakcoy plants. The research was conducted on February -March 2019 at the green house of the Food Crops and Horticulture Seeds Department of Central Java Province and the Ecology and Crop Production Laboratory of the Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. A completely randomized design of factorial pattern was used throughout the experiments. The first factor consisted of husk charcoal (M1), cocopeat (M2), and moss (M3) planting media, respectively. While the second factor consisted of 24 hours/day (A1), 12 hours/day with 30 minutes “on/off" intervals (A2), and 6 hours/day with 45 and 15 minutes “on/off" intervals (A3) of aeration. Each experimental unit was repeated 3 times. Six crops were planted on the basin, size 38 x 31 x 11 cm as one experimental unit. Parameters observed included leaves number, crop growth rate, plant production, and plant dry weight. The results showed that the treatment of moss planting media with 24 hours/day aeration gave high results on the parameters of leaves number and plant production but not significantly different from the treatment of cocopeat planting media with 12 hours /day aeration.